Distinct effects of fine and coarse aerosols on microphysical processes of shallow-precipitation systems in summer over southern China - F. Chen; F. Chen; Y. Yang; L. Yu; Y. Li; W. Liu; Y. Liu; Y. Liu; S. Lolli (Atmospheric Chemistry and Physics)
Densely populated southern China, adjacent to the South China Sea, which is associated with shallow precipitation during summer, is an open-air natural laboratory for studying the impact of aerosol particles on shallow-precipitation events. Using 8 years of data from Dual-frequency Precipitation Radar measurements, aerosol reanalysis, and atmospheric reanalysis, this study investigates the potential influence of coarse and fine aerosol particles on the structure of the precipitation and the microphysical processes of shallow precipitation in southern China. Statistical results indicate that during coarse-aerosol-polluted conditions, shallow-precipitation clouds have a lower mean height of the storm top (STH; ∼3.2 km) but a higher mean near-surface rain rate (RR; ∼1.78 mm h−1) and are characterized by high concentrations of large raindrops, driven mainly by significant collision–coalescence processes (accounting for 74.1 %). In contrast, during fine-aerosol-polluted conditions, shallow-precipitation clouds develop a deeper median STH of ∼3.7 km with lower surface RR characterized by a low concentration of small raindrops, resulting from increased breakup processes (33.1 %) and reduced collision–coalescence processes (69.6 %). The coarse (fine) aerosol particles act as promoters (inhibitors) of radar reflectivity in the profile of shallow precipitation, regardless of dynamic and humid conditions. The effect of coarse aerosol particles in promoting precipitation and the inhibiting effect of fine aerosol particles are the most significant under low-humidity conditions, mainly attributed to significantly enhanced collision–coalescence processes, exceeding 22.2 %. Furthermore, the increase in RR above 3 km in coarse-aerosol-polluted environments is mainly driven by the high concentration of hydrometeors in low-instability conditions, whereas it is driven by large hydrometeors in high-instability environments.